METHODOLOGICAL NOTES : Notes on phase transitions and the role of spin fluctuations. (7th December 2016) - Stishov, S M
Abstract: The physical properties of two chiral systems with localized and delocalized magnetic moments, Cu$ _2$ OSeO$ _3$ and MnSi, are reviewed. It is concluded that the longitudinal fluctuations of magnetic moments have no strong effect on the qualitative picture of phase transitions and the magnetic phase diagrams of chiral systems.